2010
DOI: 10.1080/02773940903413415
|View full text |Cite
|
Sign up to set email alerts
|

From Viruses to Russian Roulette to Dance: A Rhetorical Critique and Creation of Genetic Metaphors

Abstract: This essay critiques and creates metaphoric genetic rhetoric by examining metaphors for genes used by representatives of the lay American public. We assess these metaphors with a new rhetorical orientation that we developed by building onto work by Robert Ivie and social scientific qualitative studies of audiences. Specifically, our analysis reveals three themes of genetic metaphors, with the first two appearing most frequently: 1) genes as a disease or problem 2) genes as fire or bomb, and 3) genes as gamblin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Our results, thus, support French et al’s [26] suggestion that the earlier results were produced by a ceiling effect inherent to the measurement approach used there. The present results also are consonant with the qualitative research on lay people’s discourse, which showed a predominant separate tracks model but some interactive metaphors [25,27]. …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our results, thus, support French et al’s [26] suggestion that the earlier results were produced by a ceiling effect inherent to the measurement approach used there. The present results also are consonant with the qualitative research on lay people’s discourse, which showed a predominant separate tracks model but some interactive metaphors [25,27]. …”
Section: Discussionsupporting
confidence: 73%
“…This ‘separate tracks’ model is consonant with findings by Morris et al [31], who found a resistance among the public to identifying genetic components in health outcomes identified as environmental. Condit et al [25] and Gronnvoll and Landau [27] found that, in the relatively rare cases where genes and behavior were articulated in interaction with each other, participants used various metaphors for understanding genes. These included ‘virus,’ ‘trigger’ or ‘bomb’ metaphors, which portrayed genes as lying latent or dormant and then being activated by a specific exposure as well as behaviors adding ‘fuel to the fire’ of genetic backgrounds.…”
Section: Qualitative Research On Public Understanding Of Gene-environmentioning
confidence: 99%
“…The imagery that people use is not, after all, random: metaphoric language is not only ubiquitous in the way people express themselves; it affects how we understand and experience reality, it expresses how we see the world, and it influences our attitudes, knowledge, values, and actions (Foss, 2004;Gronnvol & Landau, 2010;Lakoff & Johnson, 1980). As Santa Ana (2002) puts it, "metaphor shapes everyday discourse, and by this means it shapes how people discern and enact the everyday" (p. 26).…”
Section: Data Collection and Methods Of Analysismentioning
confidence: 99%
“…One probably should call this "pseudo-universalization." I am not criticizing others here, but calling all of us to different orientations, for my own work, and that of my students, has attended almost exclusively to the U.S. (Condit, 2009;Gronnvoll & Landau, 2010). My call to internationalization has been energized by what I have heard in attendance at international conferences, where people other than rhetoricians speak.…”
Section: An Academic Route: Internationalizationmentioning
confidence: 99%